Analysis of Islamic Financial Articles Published in Scientific and Research Journals of Accounting and Finance: Content and Taxonomy Analysis - Hossein Rajabdorri (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aims to analyze Islamic financial articles published in academic and financial science and research journals using content analysis and taxonomy analysis.Methodology: This research used an analytical-descriptive approach after analyzing the quantitative classification of articles published in the scientific and financial journal of accounting and finance. Scientometrics studies quantitative aspects of science, research, and scientific policies.Findings: First, by identifying 124 papers (15 articles in scientific and journalistic accounting and 109 articles in financial science publications), using the content analysis technique, the research axes were identified in a 14-axis format. This section of the findings showed that "Islamic finance instruments" have attracted the most attention and the "Islamic finance capital market." Also, issues such as "Islamic Finance Theory" and "Islamic Financial Institutions" are at the bottom and need more attention. The study of the development of accounting and finance research journals by taxonomy analysis also showed that Islamic Finance Research is the most developed publication among the scientific and financial journals of accounting and finance in Islamic finance.Originality/Value: The findings of this research can be helpful for researchers and planners to guide future research and better management of financial and accounting journals.